Design and Development of Losartan Potassium Press Coated Tablets for Pulsatile Drug Delivery - S Ramkanth; Ashok Kumar Janakiraman; Saminathan Kayarohanam; Vetriselvan Subramaniyan; Sinouvassane Djearamane (Journal of Global Pharma Technology, 2021)
The objective of the present study was to design and evaluate time-dependent pulsatile delivery systems (PDDS) of losartan potassium pulsatile press coated tablets. Losartan potassium (LP) is angiotensin II (AG II) receptor antagonists to treat hypertension. LP pulsatile systems are time-controlled drug delivery systems which are designed to mimic the circadian rhythm of the body and deliver the drug at a specific time. LP core tablets were prepared by direct compression method using a single punch machine. The prepared tablets were shielded with a combination of different grades of Hydrosy propyl methyl cellulose (HPMC) and Ethyl cellulose (EC) as coated materials. Prepared core and pulsatile tablets were optimized and evaluated for various properties like diameter and thickness, uniformity of weight, hardness, friability, disintegration time, drug content and in vitro dissolution studies. The drug release profile LP pulsatile tablet batch of LH-3 designated as the optimized batch that shows the lag time 8 hrs with complete drug release of 99%. LP pulsatile tablets will be taken at bedtime, releasing the drug in the morning hrs when the symptoms are more prevalent can prove to be a revolution in the treatment of hypertension.